Adolescents’ perceptions of sexual coercion in Uganda - Birungi, Ruth; Nabembezi, Dennis; Kiwanuka, Julius; Ybarra, Michele; Bull, Sheana (African Journal of AIDS Research, 2011)
In Uganda, HIV prevalence remains high with young people at higher risk of infection than adults. Much is known about the sexual risk factors for HIV transmission among youths, including sexual encounters that are coerced. On the other hand, relatively little is known about the barriers to preventing sexual coercion and what strategies may overcome those barriers with adolescents. We conducted three focus group discussions with adolescents in an urban area in Uganda to understand their perceptions of sexual coercion, and to identify, from their point of view, how coercion can be addressed. Data were collected to inform the development of an Internet-based programme for young people, tailored to their HIV-information, motivation and behavioural-skills needs. The findings suggest that the participants perceived adults’ coercion of young people as common. The secondary school participants also expressed confusion over what exactly constituted coercion. They acknowledged that young people lack skills to avoid coerced sex and felt it would be critical to give youths information on the circumstances in which coercion may occur and its links to HIV risk. Finally, the youths wanted specific skills and to be empowered to avoid sexual coercion and to report rape. The findings suggest that adolescents are open to discussions about this topic and they support the call for greater integration of coercion-reduction strategies in HIV-prevention programmes targeted at their age group.
Keywords: HIV/AIDS; Prevention; Risk perceptions; Sexual health; Sexual violence; Sub-Saharan Africa; Youth